2009
DOI: 10.1103/physreve.79.051914
|View full text |Cite
|
Sign up to set email alerts
|

Neural complexity and structural connectivity

Abstract: Tononi et al. ͓Proc. Natl. Acad. Sci. U.S.A. 91, 5033 ͑1994͔͒ proposed a measure of neural complexity based on mutual information between complementary subsystems of a given neural network, which has attracted much interest in the neuroscience community and beyond. We develop an approximation of the measure for a popular Gaussian model which, applied to a continuous-time process, elucidates the relationship between the complexity of a neural system and its structural connectivity. Moreover, the approximation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(130 citation statements)
references
References 39 publications
7
123
0
Order By: Relevance
“…In neuroanatomical terms, this means that a complex neural system must be highly interconnected" (Tononi, et al 1994). Recently, Barnett et al (2009) confirmed these results.…”
Section: Introductionsupporting
confidence: 75%
“…In neuroanatomical terms, this means that a complex neural system must be highly interconnected" (Tononi, et al 1994). Recently, Barnett et al (2009) confirmed these results.…”
Section: Introductionsupporting
confidence: 75%
“…Since there is no a priori 'best' normalization for a network considered an abstraction of a neural system (e.g. [26]), we decided to compare two plausible alternatives. Further work is needed to establish the general relations among normalization, network structure and dynamical measures.…”
Section: (A) Comparison Among Measuresmentioning
confidence: 99%
“…This enables the interactions between network components (and mutual information itself) to be expressed via a covariance matrix. Recently we have highlighted and then amended an error in this analytical model by moving to a continuous time analogue of the original apparently discrete time formulation [12]. Consequently it is necessary to revisit the analytical work of De Lucia et al in light of this correction.…”
Section: Introductionmentioning
confidence: 99%